Effects of biochar combined with nitrification inhibitors on NH3 and N2O emission under different water conditions from vegetable soils - He, Zhenyuan; LÜ, Haohao; Wang, Yuying; Yuan, Hangjie; Liu, Yuxue; Li, Neng; He, Lili (Frontiers in Microbiology, 2025)
Soil nitrogen loss through NH3 volatilization and N2O emissions is a crucial issue in soil ecosystems. In this study, we explored the effects of biochar and the nitrification inhibitor DMPP (dimethyl-phenyl-piperazinium, a nitrification inhibitor) in vegetable soils under 60 and 200% WHC (water holding capacity). Five treatments were set: CK (control), urea (N), urea + biochar (N + C), urea + nitrification inhibitor (N + DMPP), and urea + nitrification inhibitor + biochar (N + C + DMPP). Results found that biochar promoted soil nitrification and ammonia volatilization under both moisture conditions, with higher NH3 rate accumulation at 200% WHC. DMPP maintained high NH4+-N concentration and increased soil ammonia volatilization, but effectively reduced N2O emissions, especially at 200% WHC. The N + C + DMPP treatment further significantly decreased N2O cumulative emissions compared to N + DMPP. QPCR results showed that N + C treatment significantly increased AOB (ammonia-oxidizing bacteria) copies compared to N treatment. Applying DMPP alone or with biochar reduced AOB copies by 50.0 and 45.7%, respectively. Soil ammonia-oxidizing archaea (AOA) responded oppositely to DMPP; AOA amounts in N + DMPP and N + C + DMPP treatments increased significantly during the culture. At 60% WHC, the greenhouse effect potential of N + DMPP and N + C + DMPP treatments were 39.0 and 43.2% lower than N, respectively. At 200% WHC, their GWP were decreased by 13.8 and 0.08% compared to N. Adding biochar alone increased the soil’s greenhouse potential at both water contents. In conclusion, using nitrification inhibitors alone or in combination with biochar is more effective in reducing the greenhouse effect potential of soil active nitrogen emissions.